Editorial - Zanotelli, Cláudio Luiz (Geografares, 2021)
The issue 32 of Geografares brings, in addition to various articles, a special dossier entitled Geographizing the pandemic – between places of existential illness, which is coordinated by Wallace Wagner Rodrigues Pantoja. This dossier contributes to understanding the effects of the Covid-19 pandemic on the most diverse sectors of daily life in the most varied environments and social situations. The mark of this pandemic will be registered for a long time in the bodies, in the spirits and in the territories in all its latitudes, including one of its central aspects is that it allowed the advance of neoliberalism and authoritarianism in Brazil, but also revealing the social r-existences the most diverses in the face of the cult of death and the social and civil war perpetrated by the current government against its own people. This issue also features an interview that we translated from French with three of the four authors of a book recently released in France and which will soon be released in Brazil [Le choix de la guerre civile. Une autre histoire du néolibéralisme (The choice of civil war. Another history of neoliberalism)], Haud Guéguen, Christian Laval and Pierre Sauvetre.